Answer:
- f(g(x)) = x - 39/4
- g(f(x)) = x - 39
- B. No
Explanation:
Given functions:
- f(x) = 1/4(x + 13)
- g(x) = 4(x - 13)
Simplified f(g(x)) and g(f(x))
- f(g(x)) = 1/4(4(x - 13) + 13) = x - 13 + 13/4 = x - 39/4
- g(f(x)) = 4(1/4(x + 13) - 13) = x + 13 - 4*13 = x - 39
Checking if f(x) and g(x) are inverse functions:
- f(x) = 1/4(x + 13), substituting f(x) and x, with x and g(x)
- x = 1/4(g(x) + 13)
- 4x = g(x) + 13/4
- g(x) = 4x - 13/4
As we see g(x) is different from the given, so the functions are not inverse